Clinical Evaluation of Oxidative Stress in Women with Breast Cancer - Muni Kumar, B. Usha, V. Murali Krishna, T. Raghava Rao*, G. Krishna Veni, D. Bhaskar Rao, D. (Recent Research in Science and Technology, 2010)
Breast cancers are potentially life-threatening malignancies in women. Development of cancer produces oxidative stress, which increases with disease progression. Hence, studies on antioxidants may be the most promising area of research for this clinical menace. We analysed serum Uric acid (UA) and Bilirubin (BR) in women with breast cancer. The changes in the levels of serum uric acid and bilirubin are measured in breast cancer patients to assess the oxidative stress. A significant increase in the levels of uric acid and an insignificant increase in the levels of bilirubin was observed in all the three categories of breast cancer patients compared to normal individuals. The results suggested that high ROS production supports the oxidative stress in breast cancer. So, the treatment with antioxidants in the initial stages of the disease may be useful as secondary therapy.